Balancing drug resistance and growth rates via compensatory mutations in the Plasmodium falciparum chloroquine resistance transporter - Petersen, Ines; Sanchez, Cecilia P.; Lanzer, Michael (Molecular microbiology, 2015)
The widespread use of chloroquine to treat Plasmodium falciparum infections has resulted in the selection and dissemination of variant haplotypes of the primary resistance determinant PfCRT. These haplotypes have encountered drug pressure and within-host competition with wild-type drug-sensitive parasites. To examine these selective forces in vitro, we genetically engineered P. falciparum to express geographically diverse PfCRT haplotypes. Variant alleles from the Philippines (PH1 and PH2, which differ solely by the C72S mutation) both conferred a moderate gain of chloroquine resistance and a reduction in growth rates in vitro. Of the two, PH2 showed higher IC50 values, contrasting with reduced growth. Furthermore, a highly mutated pfcrt allele from Cambodia (Cam734) conferred moderate chloroquine resistance and enhanced growth rates, when tested against wild-type pfcrt in co-culture competition assays. These three alleles mediated cross-resistance to amodiaquine, an antimalarial drug widely used in Africa. Each allele, along with the globally prevalent Dd2 and 7G8 alleles, rendered parasites more susceptible to lumefantrine, the partner drug used in the leading first-line artemisinin-based combination therapy. These data reveal ongoing region-specific evolution of PfCRT that impacts drug susceptibility and relative fitness in settings of mixed infections, and raise important considerations about optimal agents to treat chloroquine-resistant malaria.